The Essential Role of ClpXP in Caulobacter crescentus Requires Species Constrained Substrate Specificity - Vass, Robert H.; Nascembeni, Jacob; Chien, Peter (Frontiers in Molecular Biosciences, 2017)
The ClpXP protease is a highly conserved AAA+ degradation machine that is present throughout bacteria and in eukaryotic organelles. ClpXP is essential in some bacteria, such as Caulobacter crescentus, but dispensible in others, such as Escherichia coli. In Caulobacter, ClpXP normally degrades the SocB toxin and increased levels of SocB result in cell death. ClpX can be deleted in cells lacking this toxin, but these ΔclpX strains are still profoundly deficient in morphology and growth supporting the existence of additional important functions for ClpXP. In this work, we characterize aspects of ClpX crucial for its cellular function. Specifically, we show that although the E. coli ClpX functions with the Caulobacter ClpP in vitro, this variant cannot complement wildtype activity in vivo. Chimeric studies suggest that the N-terminal domain of ClpX plays a crucial, species-specific role in maintaining normal growth. We find that one defect of Caulobacter lacking the proper species of ClpX is the failure to properly proteolytically process the replication clamp loader subunit DnaX. Consistent with this, growth of ΔclpX cells is improved upon expression of a shortened form of DnaX in trans. This work reveals that a broadly conserved protease can acquire highly specific functions in different species and further reinforces the critical nature of the N-domain of ClpX in substrate choice.